Brillouin Optical Correlation Domain Analysis Enhanced by Time-Domain Data Processing for Concurrent Interrogation of Multiple Sensing Points - Ryu, Gukbeen; Kim, Gyu-Tae; Song, Kwang Yong; Lee, Sang Bae; Lee, Kwanil (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
We propose and experimentally demonstrate a Brillouin optical correlation domain analysis system adopting time-domain data processing and differential measurement for simultaneous interrogation of multiple sensing points. Continuous probe and pulsed pump waves are simultaneously frequency-modulated by a MHz-order sinusoidal RF wave so that multiple correlation peaks are sequentially generated according to the propagation of the pump along a fiber under test (FUT). The Brillouin gain spectrum of each correlation peak is obtained and interrogated by moving window averaging of the probe wave with a span of the period of the RF modulation, leading to the simultaneous monitoring of the multiple sensing points. In experiments, 148 correlation peaks are concurrently interrogated with a spatial resolution less than 3 cm along a 1530 m FUT.
Keywords: DIFFERENTIAL MEASUREMENT; MEASUREMENT RANGE; FIBER SENSOR; SCHEME; ENLARGEMENT; SYSTEM